Microactuation of Magnetic Nanofluid Enabled by a Pulsatory Rotating Magnetic Field - Lucian Pîslaru-Dănescu; George-Claudiu Zărnescu; Eros-Alexandru Pătroi; Rareș-Andrei Chihaia; Gabriela Telipan (Actuators, 2023)
A microactuation process was developed with the help of four coils that generate a pulsatory rotating magnetic field. A small actuator stator, which contains a 46 mm acrylonitrile butadiene styrene (ABS) opened box and four coils with E-type ferrite cores, was constructed. Simulations were made for different Duty Cycles, 0.2, 0.5, 0.72 and 0.9, and distances above the E cores, between 0.01 and 6 mm. These simulations determined the magnetic bubble inflating distance, the saturation regions and the average forces that are responsible for nanofluid flow inside the ABS box. An electrical driving scheme was designed, and a drive was constructed to activate four inductive loads that generate a pulsatory rotating magnetic field. The electronic drive can change the actuation frequency (rotation speed) between 1 Hz and 25 Hz and can adjust the Duty Cycle between 5% and 95% (driving force). From simulations and experiments, it was observed that the Duty Cycle must be limited to 0.7 to avoid the magnetic nanofluid saturation at 45 mT. It was found that three applications use a pulsatory rotating magnetic field: a small motor, a small flat pump and a manipulating sheet matrix for displays or chemical droplets mixing.